2006
DOI: 10.1007/s10682-005-2489-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Breeding Site Fidelity Drive Phenotypic and Genetic Sub-Structuring of a Population of Arctic Charr?

Abstract: There is now increasing acceptance that divergence of phenotypic traits, and the genetic structuring that underlie such divergence, can occur in sympatry. Here we report the serendipitous discovery of a sympatric polymorphism in the upper Forth catchment, Scotland, in a species for which high levels of phenotypic variation have been reported previously, the Arctic charr, Salvelinus alpinus. Attempting to determine the proximate mechanisms through which this pattern of phenotypic variation is maintained, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…Loch Doine is located in one arm of the Forth catchment (56°20 0 N, 4°20 0 W), which drains a large part of east-central Scotland eastwards to the North Sea. It has an area of 0.54 km 2 with 20 m of maximum depth (for more details, see Adams et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loch Doine is located in one arm of the Forth catchment (56°20 0 N, 4°20 0 W), which drains a large part of east-central Scotland eastwards to the North Sea. It has an area of 0.54 km 2 with 20 m of maximum depth (for more details, see Adams et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Information about diet of the fish from Loch Doine was obtained from Adams et al (2006). The methodology that they used to determine diet was as follows: stomach contents from approximately 35 charr (mean fork length 169 mm; range 88-251 mm) captured during July using multi-mesh (Norden) gill nets were removed and placed in 70% ethanol.…”
Section: Diet Determinationmentioning
confidence: 99%
“…A characteristic peculiarity of charrs of the genus Salvelinus is sympatric existence of several species, forms, or ecotypes, which are reliably distinguishable on the basis of traditional morphological characters (Behnke, 1980(Behnke, , 1989Savvaitova, 1989;Glubokovsky, 1995;Alekseyev et al, 2000;Osinov, 2002;Adams et al, 2006). It has been shown that the observed phenotypic polymorphism of charrs is often genetically determined (Dynes et al, 1999;Gislason et al, 1999;Skúlason et al, 1999;Adams & Huntingford, 2002;Klemetsen et al, 2002;Westgaard et al, 2004;Wilson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Adams & Huntingford 2004) even among sub-populations that are not geographically isolated. For example, Adams et al (2006) reported distinct differences at multiple microsatellite loci in sub-populations of the Arctic char Salvelinus alpinus from 3 closely connected lakes in Scotland. The authors proposed strong site fidelity, particularly in connection with spawning areas, as a likely mechanism producing genetic and phenotypic population sub-structuring from limited gene flow among locations even in the absence of effective physical barriers to movement.…”
Section: Introductionmentioning
confidence: 99%